2016
DOI: 10.1155/2016/8521580
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Mass Transfer in a Thin Liquid Film over an Unsteady Stretching Surface in the Presence of Thermosolutal Capillarity and Variable Magnetic Field

Abstract: The heat and mass transfer characteristics of a liquid film which contain thermosolutal capillarity and a variable magnetic field over an unsteady stretching sheet have been investigated. The governing equations for momentum, energy, and concentration are established and transformed to a set of coupled ordinary equations with the aid of similarity transformation. The analytical solutions are obtained using the double-parameter transformation perturbation expansion method. The effects of various relevant parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The flow of heat and mass in a thin liquid film has been studied [37] on an unsteady stretching surface with thermosolutal capillarity and variable magnetic field. Here, we are considering the flow model without the magnetic field and thermosolutal capillarity.…”
Section: Flow Equationsmentioning
confidence: 99%
“…The flow of heat and mass in a thin liquid film has been studied [37] on an unsteady stretching surface with thermosolutal capillarity and variable magnetic field. Here, we are considering the flow model without the magnetic field and thermosolutal capillarity.…”
Section: Flow Equationsmentioning
confidence: 99%
“…Sufian et al [7] study the impact of heat source and fluid flow over a stretch cylinder as a function of time. Zhang et al [8] demonstrated mass diffusion and solutal Marangoni impact on heat transmission and fluid flow in a film toward a stretched sheet. Kalyani et al [9] investigated the effects of Lorentz force, heat generation, and mass transfer of a Casson incompressible fluid flowing on a surface.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers reported results for local heat transfer and discussed this comprehensively. A heat and mass transport analysis under the impact of variable Lorentz forces over a thin film was presented in [4]. They highlighted the behavior of mass and temperature for multiple values of these parameters.…”
Section: Introductionmentioning
confidence: 99%